Pollination of the apple tree. III. Cultivars BR-1 and Mollie's Delicious - Pasqual, Moacir; Petri, José Luiz; Mattos, Cangussu Silveira (Pesquisa Agropecuaria Brasileira, 2014)
Pollination studies were conducted in the 1978/79 and 1979/80 growing seasons in Videira and Fraiburgo, Santa Catarina, using apple (Malus domestica, Borkh.) cultivars BR-1 and Mollie's Delicious. In Videira cultivar BR-1 was either cross pollinated with cultivars Galla, Willie Sharp, Black jon, Starkrimson, Mollie’s Delicious; open pollinated and self-pollinated. In Fraiburgo cultivar Mollie's Delicious was either cross-pollinated with cultivar, Gala, Starkrimson, Granny Smith, Delcon, Willie Sharp and open-pollinated. A complete randomization was used, with four repetitions and 50 flowers/ parcel. Fruit set, number of seed/fruit, number and germination of grains of pollen were determined. All the cultivars tested were compatible with BR-1 and Mollie’s Delicious, in major or minor degree. BR-1 presented high fruit set with all the cultivar, tested and Mollie's Delicious gave the best combination with Gala, Melrose, Starkrimson and Granny Smith, BR-1 showed high taxe of self-fertility and both cultivar, presented good germination of pollen, but low number of grains of pollen/anther.
Keywords: self-pollination; fruit set